The effect of profitability, company size, leverage, liquidity, and free cash flow on dividend policy - Trisna Rahma Sari; Dona Primasari; Yusriyati Nur Farida (Keynesia : International Journal of Economy and Business, 2023)
This study aims to examine and analyze the effect of profitability, company size, leverage, liquidity, and free cash flow on dividend policy in the health sector of companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2021 period. This study uses signaling theory as the basis of the research. The type of data used is secondary data in the form of the company's annual financial report. The sampling technique used in this study was purposive sampling method based on certain criteria. The data analysis technique that was used in this study is multiple linear regression. The research results show that: (1) Profitability has no effect on dividend policy. (2) Firm size has a positive effect on dividend policy. (3) Leverage has no effect on dividend policy. (4) Liquidity has no effect on dividend policy. (5) Free cash flow has no effect on dividend policy. The implication in this study is that company size will affect dividend policy. This research proves that the larger the size of the company, the greater the company's dividend payout policy. Meanwhile, profitability, leverage, liquidity and free cash flow have not been able to influence the company's dividend policy.